Spatiotemporal Correlation of Epileptiform Activity and Gene Expression in vitro - Schlabitz, Sophie; Monni, Laura; Ragot, Alienor; Dipper-Wawra, Matthias; Onken, Julia; Holtkamp, Martin; Fidzinski, Pawel (Frontiers in Molecular Neuroscience, 2021)
Epileptiform activity alters gene expression in the central nervous system, a phenomenon that has been studied extensively in animal models. Here, we asked whether also in vitro models of seizures are in principle suitable to investigate changes in gene expression due to epileptiform activity and tested this hypothesis mainly in rodent and additionally in some human brain slices. We focused on three genes relevant for seizures and epilepsy: FOS proto-oncogene (c-Fos), inducible cAMP early repressor (Icer) and mammalian target of rapamycin (mTor). Seizure-like events (SLEs) were induced by 4-aminopyridine (4-AP) in rat entorhinal-hippocampal slices and by 4-AP/8 mM potassium in human temporal lobe slices obtained from surgical treatment of epilepsy. SLEs were monitored simultaneously by extracellular field potentials and intrinsic optical signals (IOS) for 1–4 h, mRNA expression was quantified by real time PCR. In rat slices, both duration of SLE exposure and SLE onset region were associated with increased expression of c-Fos and Icer while no such association was shown for mTor expression. Similar to rat slices, c-FOS induction in human tissue was increased in slices with epileptiform activity. Our results indicate that irrespective of limitations imposed by ex vivo conditions, in vitro models represent a suitable tool to investigate gene expression. Our finding is of relevance for the investigation of human tissue that can only be performed ex vivo. Specifically, it presents an important prerequisite for future studies on transcriptome-wide and cell-specific changes in human tissue with the goal to reveal novel candidates involved in the pathophysiology of epilepsy and possibly other CNS pathologies.